Unusual Bilateral Oblique Craniofacial Cleft with Atypical Cleft of Palate: A Case Report with 3 Years of Follow-Up - Swain, Bharatendu; Sampreethi, Shalini; Gorle, Srujana; Saneen, Tajaly (Indian Journal of Plastic Surgery, 2025)
Oblique facial clefts are a rare entity and can be associated with palatal anomalies like synechiae caused by amniotic bands. Their treatment is individualized following sound reconstructive surgical principles. This is a case report of a 15-month-old child with cleft palate in which the right palatal shelf was represented by a tongue-like projection, associated with macrostomia and bilateral medial and lateral oro-ocular clefts. The palatal cleft was closed in two stages and the oblique clefts in the first stage. At 4 years of age, the velopharyngeal incompetence was addressed by a superiorly based pharyngeal flap. The macrostomia was corrected by a sliding V-Y flap, which effectively lengthened the buccal mucosa and ensured oral competence.
Keywords: atypical cleft palate; oblique craniofacial cleft; macrostomia